Perencanaan Sistem Optical Transport Network (OTN) Pada Sistem Transmisi DWDM - Muhammad Reza Nugraha; Irwan Syah; Siti Annisa Nindia Larasati; Didik Aribowo (Lembaga Pengembangan Kinerja Dosen, 2023)
In the era of rapid development of information and communication technology, modern society requires reliable and sophisticated means of communication. The required means of communication must be aimed at meeting current service needs, but also oriented towards meeting current and future service needs. To meet this need, a reliable network is needed, with a large bandwidth capacity with easy capacity additions, better performance, high levels of availability, and good flexibility. Fiber Optic Network is a network that is trusted to be able to handle this problem. Developments in this network were preceded by two types of transmission systems used, namely Plesiochronous Digital Hierarchy (PDH) and Synchronous Digital Hierarchy (SDH), and currently developing Dense Wavelength Division Multiplexing (DWDM) and Coarse Wavelength Division Multiplexing (CWDM) technologies.